Pengaruh Ukuran Perusahaan, Financial Leverage, Dan Liquidity Terhadap Kinerja Keuangan - Angela Maryadi, Elizabeth Sugiarto Dermawan (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The purpose of this research is to obtain empirical evidence about the effect of company size, financial leverage, and liquidity on financial performance in manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017. This research uses 45 manufacturing companies using purposive sampling method with a total of 135 data in three years. The data used is secondary data in the form of financial statements. The results of this research indicate that company size (SIZE) has a positive and significant effect on financial performance (ROA). Financial leverage (DER) has a negative and not significant effect on financial performance (ROA). While liquidity (QR) has a positive and significant influence on financial performance (ROA).